Determinants of female labor force participation in the Bangka Belitung Islands Province - Wulandari, Ayu; Valeriani, Devi; Sulistiana, Ineu (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2026)
This study examines the key factors shaping women’s labor-market participation in the Bangka Belitung Islands Province, Indonesia, where gender disparities in employment persist. It aims to analyze how demographic and economic characteristics influence women’s decisions to engage in paid work. Using a quantitative approach and a binary logistic regression model, the study draws on data from 100 women aged 15 to 65 years. The analysis evaluates the effects of age, educational attainment, marital status, number of dependents, and household income. The findings indicate that education and household income are significant determinants of women’s labor force participation. Women with a junior high school education are significantly less likely to participate in the labor market than those with a tertiary education. Meanwhile, higher household income contributed by other family members reduces women’s likelihood of working. However, age, marital status, and the number of dependents do not have statistically significant effects. These results underscore the importance of human capital and household economic conditions in shaping women’s labor market behavior in resource-based regions. The study also provides policy-relevant insights for promoting more inclusive labor markets through investments in education, skills development, and gender-responsive employment strategies.